2014
DOI: 10.7727/wimj.2013.089
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Ameliorates Nicotine Exposure Induced Impaired Spatial Memory Performances in Rats

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…Attenuation of oxidative stress and alleviation of the antioxidant defenses is another mechanism we hypothesized to contribute to the protective effect of C. sinensis on nicotine-induced neurodevelopmental and behavioral changes in mice newborn. Our hypothesis is supported by findings of multiple studies demonstrating alleviated neurobehavioral performance in experimental animals supplemented with antioxidants [ 30 , 62 ]. Previous studies have attributed memory impairment following prenatal nicotine exposure to excessive production of ROS and its subsequent cell death in various brain regions [ 28 30 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Attenuation of oxidative stress and alleviation of the antioxidant defenses is another mechanism we hypothesized to contribute to the protective effect of C. sinensis on nicotine-induced neurodevelopmental and behavioral changes in mice newborn. Our hypothesis is supported by findings of multiple studies demonstrating alleviated neurobehavioral performance in experimental animals supplemented with antioxidants [ 30 , 62 ]. Previous studies have attributed memory impairment following prenatal nicotine exposure to excessive production of ROS and its subsequent cell death in various brain regions [ 28 30 ].…”
Section: Discussionsupporting
confidence: 83%
“…Our hypothesis is supported by findings of multiple studies demonstrating alleviated neurobehavioral performance in experimental animals supplemented with antioxidants [30, 62]. Previous studies have attributed memory impairment following prenatal nicotine exposure to excessive production of ROS and its subsequent cell death in various brain regions [2830].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Mothers’ smoking was not affecting children’s memory because most mothers were not smokers as this practice is not socially acceptable among women in Jordanian culture. Available literature found that smoking status of parents was negatively associated with memory and academic performance of children [ 14 , 15 , 37 , 38 ]. For example, a large study found that children with different memory disabilities were more exposed to second hand smoking than their peers [ 39 ] highlighting the negative effect of nicotine exposure on working memory [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…One "candidate" beneficial dietary exposure is vitamin C. Vitamin C is an anti-oxidant that helps antagonise the nicotine induced damage [18,19], or alterations in lung metabolism [20] and there is some indication that it prevents offspring DNA methylation changes associated with maternal smoking in pregnancy [21]. Previous work also suggests that vitamin C can reduce the nicotine exposure induced impaired neurological functioning in rats [22], and reduce the risk of developing sudden infant death syndrome [23]. In other animal experiments vitamin C seems to antagonise the negative effects of prenatal exposure to nicotine on the development of the lungs [24,25].…”
mentioning
confidence: 99%